Implementasi Pendidikan Kecerdasan Sosial Emosional Berbasis Nilai Nilai Keislaman Anak Usia 5-6 Tahun Di Tk Tunas Karya Wates - Rizqi Annisa Fitri, Siti Roudhotul Jannah, Jaenullah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Early childhood social and emotional development plays a crucial role in shaping character and social skills. However, amidst the negative influence of social media, lack of parental supervision, and environmental changes, these skills are vulnerable to decline. Therefore, implementing social and emotional intelligence education based on Islamic values is a strategic effort to instill noble morals from the age of 5-6 through structured habits in daily life. Tunas Karya Kindergarten, Wates, is one of the institutions that strives for social and emotional learning based on Islamic values through learning activities that encompass aspects of monotheism, worship, and noble morals as a form of habituation that supports child growth and development. The objectives of this study are: 1) to analyze the planning of social and emotional intelligence education based on Islamic values for children aged 5-6 at Tunas Karya Kindergarten, Wates. 2) to analyze the implementation of social and emotional intelligence education based on Islamic values for children aged 5-6 years at Tunas Karya Kindergarten in Wates, and 3) to analyze the evaluation of social and emotional intelligence education based on Islamic values for children aged 5-6 years at Tunas Karya Kindergarten in Wates. This study is a qualitative study with a phenomenological approach. Data collection techniques used observation, interviews, and documentation. Data validity was tested using source triangulation. Data analysis techniques included data reduction, data presentation, and conclusions. The results of this study indicate that the planning, implementation, and evaluation of social emotional intelligence education based on Islamic values ​​in Tunas Karya Wates Kindergarten are carried out systematically and in a directed manner. 1) Teachers design learning according to the developmental stages of children aged 5-6 years by integrating Islamic values ​​such as honesty, mutual assistance, and politeness through clear materials, appropriate methods, and creative media. 2) The implementation of social emotional intelligence education based on Islamic values ​​for children aged 5-6 years in Tunas Karya Wates Kindergarten is carried out through three stages: an introduction with Islamic activities such as praying and greeting, a core with an introduction to the values ​​of monotheism, worship, and morals through various creative and social activities, and a closing reflection as a simple way for children to express emotions and understand the values ​​taught, all done in a fun and humanistic way. 3) Evaluation is carried out continuously through direct observation and recorded in a daily development book and character assessment sheet, the results of which are communicated to parents to strengthen cooperation in the formation of children's character.